Diminished concentrations of insulin-like growth factor I in cystic fibrosis. Issue 6 (June 1995) - Laursen, E M; Juul, A; Lanng, S; Høiby, N; Koch, C; Müller, J; Skakkebaek, N E
Abstract : Cystic fibrosis is frequently accompanied by a catabolic condition with low body mass index caused by a number of disease complications. Insulin-like growth factor-I (IGF-I) is an anabolic hormone and an important marker of nutritional status, liver function, and linear growth. Available data on IGF-I in cystic fibrosis are sparse and conflicting. From 1990-3, 235 of our 240 patients (114 males, 121 females, median age 16.2 years, ranged 0.1-44.0 years) had IGF-I measured once by radioimmunoassay. IGF-I was significantly reduced compared with a healthy Scandinavian control population: mean (-2 SD to +2 SD) IGF-I SD score was -0.97 (-3.7 to 1.7) in males and -0.67 (-3.2 to 1.9) in females. Height SD score was -0.95 (-3.3 to 1.4) in males and -0.81 (-3.2 to 1.6) in females. In patients who were still in the growth period a significant correlation of IGF-I SD score to height SD score (r = 0.28, p < 0.001) was found. The low IGF-I concentrations may reflect the catabolic state of many patients with cystic fibrosis and play a part in their abnormal growth pattern.